Pengembangan Prototipe Token Transaksi Cryptocurrency SDSPay Berbasis Blockchain Ethereum - Virgian Galang Sasongko; Faulinda Ely Nastiti; Sopingi Sopingi (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The transformation of digital payment systems through blockchain technology has brought new challenges and opportunities in the development of secure, efficient, and decentralized crypto tokens. One emerging approach is the use of smart contract-based tokens, such as ERC-20 tokens running on the Ethereum network. This research proposes the design and implementation of the SDSPay (SDS) token as a prototype Ethereum-based ERC-20 token, with a modern smart contract approach to meet the needs of a more efficient and secure digital payment system. The SDS token adopts the basic ERC-20 standard but is equipped with advanced features that enhance functionality and security, such as role-based access control (RBAC) to regulate access and control over transactions, pauseable transactions to pause transactions if necessary, and compatibility with EIP-2612 permits that enable more efficient transaction authorization in terms of gas. These features are designed to improve the efficiency and security of transactions on blockchain networks, thus enabling the use of tokens in a more reliable digital payment system. The SDS token prototype was tested on the Sepolia Testnet using Remix IDE and MetaMask to develop and manage smart contracts. Additionally, a static security audit was conducted using Slither Analyzer to detect potential vulnerabilities. The test results showed that the SDS token was successfully deployed and performed well, with an average transaction time of 10–12 seconds and stable gas fees. The Slither audit also found no significant vulnerabilities, indicating that the smart contract structure adheres to security best practices. This study confirms that the development of standardized smart contract-based tokens can be carried out using an efficient, reliable, and replicable methodology for other applications in future blockchain-based payment systems. This implementation of the SDSPay (SDS) token can serve as a foundation for designing secure and efficient digital payment systems, paving the way for the broader development of blockchain technology.